The Effects of Financial and Environmental Performances on Firm Value with Environmental Disclosure as an Intervening Variable - Rinsman, Theresia Coline Sari; Prasetyo, Andrian Budi (Jurnal Dinamika Akuntansi, 2020)
This study aims to analyze the effects of financial performance and environmental performance to firm value with environmental disclosure as an intervening variable. Financial performance which measured by Ratio On Sales (ROS) and environmental performance which measured by PROPER ranking act as independent variables and firm value which measured by stock price acts as dependent variable also environmental disclosure which measured by GRI Standards as an intervening variable. This study uses secondary data and selects the sample used purposive sampling method. The samples consist of non financial companies listed in the Indonesia Stock Exchange (IDX), participated in the PROPER (Program Penilaian Peringkat Kinerja Perusahaan / Performance Rating Assestment Program on Environment Management) and published both annual report and sustainability report for 2017-2018. Partial Least Squares technique is chosen for the study statistic analysis. Results from this research show that financial performance has a negative impact on environmental disclosure, environmental performance has a significant positive impact on environmental disclosure and environmental disclosure does not affect the firm value. Next, the environmental disclosure is not able to intervene the effects of financial performance and environmental performance on firm value. The implications of this research are prove that the environmental aspects of information disclosed by the company have not been an important assessment for investors in viewing the performance of a company and also suggest investors to consider the company's environmental disclosure in making investment decisions because it contain an important aspect of corporate sustainability.